CMOS design of a phase shifter for 5G/6G active antenna arrays - del Río Bueno, Carolina; Esteban Eraso, Uxua; Celma Pueyo, Santiago; Sánchez Azqueta, Carlos (Jornada de Jóvenes Investigadores del I3A, 2022)
This paper presents the design of a phase shifter operating over the 18-27 GHz frequency range. The phase shifter is digitally programmable using a 65 nm CMOS process. Schematic simulation results provide an RMS value at 24 GHz of 3.5º for the phase and of 0.76 dB for the gain.